Ответ:
а=11
Пошаговое объяснение:
пусть значение выражения 2а+3=b, тогда(по условию) значение выражения 7а-2=3b
т.к. b*3=3b, то и (2а+3)*3=3b
тогда 7а-2=3b=(2а+3)*3
7а-2=(2а+3)*3
7а-2=6а+9
7а-6а=9+2
проверка:
11*2+3=22+3=25; 11*7-2=77-2=75; 75/25=3
ответ верен
11
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
а=11
Пошаговое объяснение:
пусть значение выражения 2а+3=b, тогда(по условию) значение выражения 7а-2=3b
т.к. b*3=3b, то и (2а+3)*3=3b
тогда 7а-2=3b=(2а+3)*3
7а-2=(2а+3)*3
7а-2=6а+9
7а-6а=9+2
а=11
проверка:
11*2+3=22+3=25; 11*7-2=77-2=75; 75/25=3
ответ верен
Ответ:
11
Пошаговое объяснение: